Influência de fatores antinutricionais da leucena (Leucaena leucocephala e Leucaena cunningan) e do feijão guandu (Cajanus cajan) sobre o epitélio intestinal e o desempenho de frangos de corte - Oliveira, Paulo Batista de; Murakami, Alice Eiko; Garcia, Elis Regina de Moraes; Macari, Marcos [UNESP]; Scapinello, Cláudio (Sociedade Brasileira de Zootecnia, 2000)
Um experimento foi conduzido para avaliar a influência de fatores antinutricionais de alguns alimentos sobre o epitélio intestinal e o desempenho de frangos de corte. Foram utilizados 480 pintos de um dia de idade, em um delineamento inteiramente casualizado com quatro tratamentos (A = ração testemunha à base de milho e soja; B = ração contendo Leucaena leucocephala - 6% [LL]; C = ração contendo Leucaena cunningan - 6% [LC] e D = ração contendo feijão guandu - Cajanus cajan - 20% [CC]), quatro repetições e 30 aves por unidade experimental. Houve redução de ganho de peso e aumento da conversão alimentar com a utilização de LL e LC, no período de 1a 21 e de 1a 42 dias de idade. Aos 21 dias de idade, observou-se aumento no tamanho dos vilos do jejuno e na relação vilo:cripta do jejuno e íleo, nas aves que receberam LC. Houve aumento significativo (P<0,05) das células caliciformes no duodeno e jejuno em aves de todos os tratamentos e apenas LL e LC aumentaram as células caliciformes do íleo. Aos 42 dias de idade, houve aumento no número de células caliciformes causado por CC no duodeno e por LL, LC e CC no íleo. O consumo de ração e a profundidade de cripta não foram influenciados. A alteração da morfologia da vilosidade do jejuno, bem como a alteração na relação vilo:cripta no período inicial, influenciou negativamente o ganho de peso e a conversão alimentar nos períodos inicial e total.

A trial was conducted to evaluate the influence of antinutritional factors in some feedstuffs on broiler chick's performance and intestinal epithelium. A total of 480 one-day old broiler chicks were allotted to a completely randomized experimental design with four treatments (A= corn and soybean meal based control diet; B = diet containing Leucaena leucocephala - 6% [LL]; C = diet containing Leucaena cunningan - 6% [LC] and D = diet containing Pigeous bean - Cajanus cajan - 20% [CC]), four replicates and 30 broiler chicks per experimental unit. The broiler chicks, which were fed with LL and LC containing diets showed lower weight gain and a worse feed: gain in the periods from 1 to 21 and from 1 to 42 days of age. At 21st days of age only the broiler chicks fed with LC containing diet showed a higher villi size in jejunum and villi: crypt ratio in jejunum and ileum. There was significant increase on the number of Goblet cells in the duodenum and jejunum in the broiler chicks of all treatments at the 21st day of age, and only broiler chicks fed with LL and LC containing diets showed an increased number of Goblet cells in the ileum. At 42th day of age, an increase of Goblet cells was observed in the duodenum of broiler chicks fed with CC containing diets, and in the ileum of broiler chicks fed with LL, LC e CC containing diets. Feed intake and crypt depth were not influenced by treatments in any of the experimental periods. Alterations on jejunum villi morphology, villi: crypt ratio and increased number of Goblet cells in the initial period resulted on a worse weight gain and feed: gain in the initial and total growth periods of the broiler chicks.
Influence of antinutritional factors of leucaena (Leucaena leucocephala and Leucaena cunningan) and pigeous bean (Cajanus cajan) on the intestinal epithelium and performance of broiler chickens
Keywords: Cajanus cajan; intestinal epithelium; Antinutritional factors; broilers chicks; Leucaena cunningan and leucocephala; Cajanus cajan; epitélio intestinal; Fatores antinutricionais; Frangos de corte; Leucaena cunningan e leucocephala